2013
DOI: 10.1016/j.bbrc.2013.01.134
|View full text |Cite
|
Sign up to set email alerts
|

Human P2X7 receptor activation induces the rapid shedding of CXCL16

Abstract: Activation of the purinergic P2X7 receptor by extracellular ATP induces the shedding of cell-surface molecules including the low-affinity IgE receptor, CD23 from leukocytes. CD23 is a known substrate of a disintegrin and metalloprotease (ADAM)10. The aim of the current study was to determine if P2X7 activation induced the shedding of the chemokine CXCL16, an ADAM10 substrate. Using immunolabelling and flow cytometry we demonstrate that human RPMI 8226 multiple myeloma B cells, which have been previously shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…ATP-induced CD23 shedding was indirectly assessed by measuring the loss of cell-surface CD23 using an anti-CD23 mAb and flow cytometry following 7 min incubation with 1 mM ATP, which is approximate to the t 1/2 for this process [17,29]. As previously observed [17,29], ATP induced CD23 shedding from RPMI 8226 cells in NaCl medium (Fig.…”
Section: P2x7 Antagonists Inhibit Atp-induced Pore Formation In a Consupporting
confidence: 54%
See 3 more Smart Citations
“…ATP-induced CD23 shedding was indirectly assessed by measuring the loss of cell-surface CD23 using an anti-CD23 mAb and flow cytometry following 7 min incubation with 1 mM ATP, which is approximate to the t 1/2 for this process [17,29]. As previously observed [17,29], ATP induced CD23 shedding from RPMI 8226 cells in NaCl medium (Fig.…”
Section: P2x7 Antagonists Inhibit Atp-induced Pore Formation In a Consupporting
confidence: 54%
“…More recently, we have shown that P2X7-induced CD23 shedding is mediated by ADAM10 [29]. However, it is unknown if P2X7-induced CD23 shedding results from changes in intracellular cation concentrations, stimulation of signalling pathways downstream of P2X7 activation or by a direct physical interaction of P2X7 itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human P2X7 activation induces the rapid shedding of CD23 and CXCL16 from malignant B cells [19][20][21] , as well as the shedding of the interleukin-6 receptor (IL-6R) from human epithelial cells or murine fibroblasts co-transfected with human P2X7 and human IL-6R [22] . Human P2X7-induced CD23, CXCL16 and IL-6R shedding is primarily mediated by ADAM10 [21,22] , however it is likely that ADAM17 is the principle sheddase involved in P2X7-induced CD62L shedding from human CD4 + and CD8 + T cells. It has previously been shown that P2X7-induced CD62L and CD23 shedding from malignant B cells is mediated by different metalloproteases [20] , and that ADAM17 is the principle sheddase for both calcium-and ATP-induced CD62L shedding from murine B cells [23] .…”
Section: ) Comparison Of Cd4mentioning
confidence: 99%